Electrochemical sensor for dodecyl gallate determination based on electropolymerized molecularly imprinted polymer - Pedroso, Mariele Mucio [UNESP]; Foguel, Marcos Vinicius [UNESP]; Silva, Dulce Helena Siqueira [UNESP]; Sotomayor, Maria del Pilar Taboada [UNESP]; Yamanaka, Hideko [UNESP] (Elsevier, 2017)
An electrochemical sensor based on molecularly imprinted polymer (MIP) film for dodecyl gallate detection at the surface of a glassy carbon electrode (GCE) was proposed in this paper. The GCE was modified with f-MWCNT and the MIP synthesis was performed in situ by means of electropolymerization using ortho-phenylenediamine as the monomer. The stepwise preparation of the MIP and NIP (non-imprinted polymer) was characterized electrochemically by means of cyclic and square wave voltammetry employing ferrocyanide/ferricyanide as a redox probe. The selective capacity performance of the MIP and its imprinted effect to the template molecule (analyte) was compared to the NIP. They were also characterized by scanning electron microscopy technique (SEM). The analytical performance of the MIP sensor performed using square wave voltammetry showed linear range from 0.50 to 8.0 × 10−9 mol L−1, with a correlation coefficient of 0.9921. The sensor presented detection and quantification limit of 0.22 × 10−9 and 0.67 × 10−9 mol L−1, respectively. The apparent dissociation constant (KD) calculated was of 1.26 × 10−4 mol L−1 and 5.27 × 10−1 mol L−1 for the MIP and NIP respectively.
Keywords: Antioxidant; Electropolymerization; Galloyl group; Square wave voltammetry; Syntetic recognizer